2023
DOI: 10.12968/jowc.2023.32.9.560
|View full text |Cite
|
Sign up to set email alerts
|

The theory and practice of pressure ulcer/injury risk assessment: a critical discussion

Jan Kottner,
Susanne Coleman

Abstract: Pressure ulcer/injury (PU) risk assessment is widely considered an essential component in clinical practice. It is a complex and broad concept that includes different approaches, such as clinical judgement, using standardised risk assessment instruments, skin assessments, or using devices to measure skin or tissue properties. A distinction between PU risk assessment and early detection is important. PU risk measures the individual's susceptibility to developing a PU under a specific exposure (primary preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
0
0
1
Order By: Relevance
“…Research has shown that cardiovascular dysfunction negatively affects PI healing, 16,37 probably due to reduced tissue perfusion, tissue ischemia, hypoxia, interrupted nutrition or oxygen supply, and metabolic waste accumulation 38 . In the present study, however, patients with a cardiovascular comorbidity had a higher PI healing rate than those without.…”
Section: Discussioncontrasting
confidence: 68%
“…Research has shown that cardiovascular dysfunction negatively affects PI healing, 16,37 probably due to reduced tissue perfusion, tissue ischemia, hypoxia, interrupted nutrition or oxygen supply, and metabolic waste accumulation 38 . In the present study, however, patients with a cardiovascular comorbidity had a higher PI healing rate than those without.…”
Section: Discussioncontrasting
confidence: 68%